Комп’ютерний застосунок для комунікації студентів та викладачів в університеті - Марчук, С. С. (ХНУРЕ, 2020)
Messengers it's the most demanded applications in XXI century. Using messengers’ peoples can instantly communicate, share video and audio files with each other. It was decided develop application which is aimed at the audience students and teachers of Kharkiv National Univercity of Radioelectronics. With it help students and teachers no longer must look for each other in social networks or messengers which now there are quite a large number. When user is authorizing in application, he has opportunity to communicate with their classmates and can find teacher for chat with him.
Keywords: CIST API; Firebase; Cloud Firestore; мобільні пристрої